SARS-CoV-2 non-structural protein 6 triggers NLRP3-dependent pyroptosis by targeting ATP6AP1 - Sun, Xiao (2022)
A recent mutation analysis suggested that Non-Structural Protein 6 (NSP6) of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a key determinant of the viral pathogenicity. Here, by transcriptome analysis, we demonstrated that the inflammasome-related NOD-like receptor signaling was activated in SARS-CoV-2-infected lung epithelial cells and Coronavirus Disease 2019 (COVID-19) patients' lung tissues. The induction of inflammasomes/pyroptosis in patients with severe COVID-19 was confirmed by serological markers. Overexpression of NSP6 triggered NLRP3/ASC-dependent caspase-1 activation, interleukin-1β/18 maturation, and pyroptosis of lung epithelial cells. Upstream, NSP6 impaired lysosome acidification to inhibit autophagic flux, whose restoration by 1α,25-dihydroxyvitamin D3, metformin or polydatin abrogated NSP6-induced pyroptosis. NSP6 directly interacted with ATP6AP1, a vacuolar ATPase proton pump component, and inhibited its cleavage-mediated activation. L37F NSP6 variant, which was associated with asymptomatic COVID-19, exhibited reduced binding to ATP6AP1 and weakened ability to impair lysosome acidification to induce pyroptosis. Consistently, infection of cultured lung epithelial cells with live SARS-CoV-2 resulted in autophagic flux stagnation, inflammasome activation, and pyroptosis. Overall, this work supports that NSP6 of SARS-CoV-2 could induce inflammatory cell death in lung epithelial cells, through which pharmacological rectification of autophagic flux might be therapeutically exploited.